Long‐term oncological outcomes after laparoscopic radical prostatectomy - Hruza, Marcel; Bermejo, Justo Lorenzo; Flinspach, Bettina; Schulze, Michael; Teber, Dogu; Rumpelt, Hans Joachim; Rassweiler, Jens Jochen (BJU international, 2013)
What's known on the subject? and What does the study add? Laparoscopic radical prostatectomy (LRP) has shown good oncological short‐term and mid‐term outcomes, but long‐term outcomes are still lacking. We present long‐term oncological outcomes of LRP in a large cohort of patients operated on in one of the pioneering European centres. The data from the present study show high rates of biochemical and clinical recurrence‐free survival and low cancer‐specific mortality compared with open series. Objectives To investigate long‐term oncological outcomes after laparoscopic radical prostatectomy (LRP). To identify parameters influencing recurrence‐free survival in a single‐institution series. Patients and Methods All patients underwent LRP using the transperitoneal retrograde Heilbronn technique. High‐risk patients received adjuvant treatment according to an institutional algorithm based on prostate‐specific antigen (PSA), Gleason score, tumour‐node‐metastasis stage, margin status and tumour volume. Data were collected prospectively on operative and postoperative parameters beginning in 1999. Complete follow‐up data of 370 of the first 500 consecutive patients are available. Biochemical recurrence was defined as two consecutive PSA levels <0.2 ng/mL within the follow‐up period. Kaplan–Meier estimates and Cox regression were applied to examine recurrence‐free survival times. Results The estimated biochemical recurrence‐free survival (BCRFS) rates 10 years after LRP were 80.2% in patients staged pT2, 47.4% in those staged pT3a and 49.8% in those staged pT3b/4, confirming a better prognosis in patients with organ‐confined disease (P < 0.001). In the multivariate Cox regression analysis, only Gleason score and pT stage significantly influenced BCRFS. The 10‐year clinical progression‐free survival rates were 97.2% (pT2), 84.4% (pT3a) and 78.1% (pT3b/4), and prostate cancer‐specific survival estimates were 100% (pT2), 97.3% (pT3a) and 90.6% (pT3b/4). Conclusions The 10‐year biochemical and clinical progression‐free survival after LRP combined with a risk‐adapted concept of adjuvant therapy is high, while prostate‐cancer specific mortality is low. Our data shows no negative impact of laparoscopic techniques on oncologic outcomes compared to large series after retropubic radical prostatectomy. In a multivariate Cox regression, only Gleason score and pT stage had significant impact on BCRFS.